EVALUASI SISTEM PERLINDUNGAN PADA BTS (BASE TRANSCEIVER STATION) ARENA REMAJA PONTIANAK PT.INDOSAT TERHADAP SAMBARAN PETIR - ., Joninton (Faculty of Engineering, Universitas Tanjungpura, 2016)
Abstract This study discusses about external and internal protection at BTS Arena Remaja Pontianak PT.Indosat. External protection was analyzed withRolling Sphere Method and BTS’s height is 40 meters. The efficiency of BTS Arena Remaja is 0,93 with protection level II and the radius of rolling sphere is 30 meters so it could be said that the protection chamber such as shelter and generator room are safe from direct lightning. Furthermore, the grounding resistance number from that measurements is around 0,02-0,07 ohm. At internal protection known that overvoltage will be occurs with peak currents in Kalimantan Barat, determined base on the average of peak currents in the earth, as non ideal value is 36,16 kA which can damage the equipment in protection chamber through the electric power line and signal line (coaxial cable). More voltage in the electrical transmission is 7753,78 kV and in the signal (coaxial cable) minimum 0.07764 kV and maximum0.07909 kV with the fault of current is 36.16 kA. That voltage will continue flowing to the equipment, so there should be some equipment protection. For an alternative, mounting arresters can be done in stages according to the characteristics. Keyword : Eksternal Protection, Internal Protection, Rolling Sphere Method